Green Emerging Digital Technologies, Green Supply Chains, and the Performance of Environmentally Friendly Firms: The Underpinning Role of Human Resources - Fiorini, Paula C.; Chiappetta Jabbour, Charbel J.; Latan, Hengky; de Sousa Jabbour, Ana Beatriz L.; Mariano, Enzo B. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Anchored in the resource-based view, this research analyzes the relationships between green information systems (Green IS), green human resource management (GHRM), and green supply chains (GSCM). It then examines the effects of these relationships on the environmental and financial performance of organizations. To meet the proposed objectives, a survey was carried out with 211 Brazilian companies, with the data analysis stage employing the structural equation modeling technique. The main findings include that green information systems play an important role in supporting green supply chain practices, and indirectly contribute to environmental and financial performance by facilitating organizational processes. Furthermore, our results reveal that human resources partially mediate the relationship between information systems and green supply chains, through employee engagement in environmental management and rewards based on environmental performance. This study also brings a number of theoretical and practical contributions. In terms of theory, it highlights a previously unexplored relationship between the prevailing concepts of Green IS, GSCM, and GHRM, and their impacts on firm performance, which enriches the body of knowledge in the IS, HR, and engineering management fields. For practitioners, this study reveals how they can strategically articulate HR, IS, and supply chain functions to support sustainability strategies. The findings clarify that blending technical (IS) and soft (HR) skills is pivotal to developing valuable GSCM capabilities to support and improve companies’ performance.
Keywords: Companies; Emerging technologies; green human resource management; green information systems; Green products; Information systems; performance; Standards organizations; supply chain; Supply chain management; Supply chains; sustainability; Sustainable development